Improving Knowledge and Process for International Emergency Medicine Fellowship Applicants: A Call for a Uniform Application - Gabrielle A. Jacquet; Jamil D. Bayram; William B. Ewen; Bhakti Hansoti; Steven Andescavage; David Price; Robert E. Suter; Alexander Vu (Emergency Medicine International, 2013)
Background. There are currently 34 International Emergency Medicine (IEM) fellowship programs. Applicants and programs are increasing in number and diversity. Without a standardized application, applicants have a difficulty approaching programs in an informed and an organized method; a streamlined application system is necessary. Objectives. To measure fellows’ knowledge of their programs’ curricula prior to starting fellowship and to determine what percent of fellows and program directors would support a universal application system. Methods. A focus group of program directors, recent, and current fellows convened to determine the most important features of an IEM fellowship application process. A survey was administered electronically to a convenience sample of 78 participants from 34 programs. Respondents included fellowship directors, fellows, and recent graduates. Results. Most fellows (70%) did not know their program’s curriculum prior to starting fellowship. The majority of program directors and fellows support a uniform application service (81% and 67%, resp.) and deadline (85% for both). A minority of program directors (35%) and fellows (30%) support a formal match. Conclusions. Program directors and fellows support a uniform application service and deadline, but not a formalized match. Forums for disseminating IEM fellowship information and for administering a uniform application service and deadline are currently in development to improve the process.